Pengembangan Gim Edukasi Kebersihan Lingkungan untuk Kesadaran Masyarakat Akibat Pencemaran: Indonesia - Zefanya, Marcellino; Dirgantara, HB (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2025)
The purpose of this research is to develop a educational game with game maker game engine as an alternative media for general public awareness, researchers take a material model that will be applied to 2D games and platformers. The method used by researchers is the Game Development Life Cycle (GDLC) method with stages: initiation, pre-production, production, black box testing, beta, and release. The final result of this research is an educational game entitled "Clean The Trash" which can be played on Windows program applications. Based on the questionnaire results from the black box testing of 10 respondents, 10 out of 10 people can be more aware of the types of garbage and the dangers of garbage can pollute the environment after playing the educational game "Clean The Trash!"